2014
DOI: 10.1124/dmd.114.059147
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Intestinal Availability (FG) of Substrate Drugs of Cytochrome P450s by Analyzing Changes in Pharmacokinetic Properties Caused by Drug–Drug Interactions

Abstract: In this study, we developed the drug-drug interaction (DDI) method as a new assessment technique of intestinal availability (F G , the fraction of drug transferred from the intestinal enterocytes into the liver, escaping from intestinal metabolism) based on the clearance theory. This method evaluates F G from changes caused by DDIs in the area under the blood concentration-time curve and in the elimination half-life of victim drugs. Application of the DDI method to data from the literature revealed that the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…F a F g or F g values were calculated with one of the following methods (in the order of preference, depending on the data available) for CYP3A4/5 drugs that had clinical CKD reports ( Table ): IV/PO method: F a F g = F / [1−CL iv,B × (1−f e,urine ) / Q h ], where CL iv,B , f e,urine , F, and Q h represent blood clearance after intravenous administration, fraction eliminated into urine as an unchanged drug, absolute bioavailability, and hepatic blood flow rate, respectively (25.5 ml/min/kg). If the blood‐to‐plasma concentration ratio was not reported, this value was predicted using GastroPlus v. 9.0 (Simulations Plus, Lancaster, PA). An F g estimation method proposed by Hisaka et al , which utilizes changes in both AUC and terminal half‐life with DDI to differentiate the inhibitor effects on hepatic and intestinal CYP3A4/5. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…F a F g or F g values were calculated with one of the following methods (in the order of preference, depending on the data available) for CYP3A4/5 drugs that had clinical CKD reports ( Table ): IV/PO method: F a F g = F / [1−CL iv,B × (1−f e,urine ) / Q h ], where CL iv,B , f e,urine , F, and Q h represent blood clearance after intravenous administration, fraction eliminated into urine as an unchanged drug, absolute bioavailability, and hepatic blood flow rate, respectively (25.5 ml/min/kg). If the blood‐to‐plasma concentration ratio was not reported, this value was predicted using GastroPlus v. 9.0 (Simulations Plus, Lancaster, PA). An F g estimation method proposed by Hisaka et al , which utilizes changes in both AUC and terminal half‐life with DDI to differentiate the inhibitor effects on hepatic and intestinal CYP3A4/5. …”
Section: Methodsmentioning
confidence: 99%
“…Among the remaining 33 drugs, F a F g values of 22 drugs were estimated either by the intravenous/oral (IV/PO) method. Because of the instability in estimating F g with Method 2 for high clearance drugs, we estimated F g value only for 5 out of remaining 11 drugs with the method of Hisaka et al, 29 for which observed oral clearance was lower than hepatic blood flow rate. In total, F a F g or F g were calculated for 29 drugs.…”
Section: Collection Of Clinical Ckd Studies For Model Drugsmentioning
confidence: 99%
“…The apparent total body clearance (CL/F) was calculated by dividing the dosage of etizolam (0.25 mg/person) by AUC ∞ , and the apparent volume of distribution (V d /F), was calculated by dividing CL/F by k e . Intestinal availability (F g ) was estimated by the following equation: FgAUCN×t1/2AUCN×t1/2Fag×t1/2t1/2/0ptFag×()t1/2t1/2QHQH…”
Section: Methodsmentioning
confidence: 99%
“…Parameters indicated with an asterisk are in the presence of DDI. F* ag was estimated as reported, and 21.4 mL/min/kg was used as the value of Q H .…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic intrinsic clearance, membrane permeability, and the blood-free fraction were taken from the literature (Gertz et al, 2011). The observed F G was estimated using the drug-drug interaction method reported by Hisaka et al (2014) and taken from other sources (Varma et al, 2010). The other observed or reported values required for analysis in this study are shown in Tables 3 and 4.…”
mentioning
confidence: 99%